RANCANG BANGUN GAME EDUKASI BAHASA ARAB 2D BERBASIS UNITY MENGGUNAKAN METODE MDLC PADA MAN PURBALINGGA - Husna Maulida; Pungkas Subarkah; Banu Dwi Putranto (LPPM Universitas Abdurrab, 2026)
Arabic language learning at MAN Purbalingga still relies heavily on conventional lecture-based methods and printed textbooks, causing 62.9% of eleventh-grade students to feel disengaged from the current vocabulary (mufradat) memorization approach. This study aims to design and implement a mobile educational game entitled Arabic Quest as an interactive and engaging learning medium for Hajj and Umrah mufradat. Development was carried out using Unity 2022 LTS and C# programming language, following the Luther-Sutopo version of the Multimedia Development Life Cycle (MDLC) method, which encompasses six stages: concept, design, material collection, assembly, testing, and distribution. The final product is an Android application (minimum version 8.0 Oreo) that integrates 2D adventure exploration mechanics, a trigger-based quiz system, and a Hajj and Umrah ticket reward as feedback for mission completion. Beta Testing was conducted with 33 eleventh-grade students of MAN Purbalingga using a Likert scale 1–5 questionnaire across four indicators. Results show an average feasibility score of 86.1%, with individual scores of 86.7% for Visual Quality, 86.2% for Usability, 85.9% for Engagement, and 85.8% for Content Quality, all classified as Very Feasible. It is concluded that Arabic Quest is suitable as an effective self-learning medium and represents an innovative alternative to conventional Arabic language instruction at the madrasah aliyah level.